Dissolved organic matter and trace element variability in a blackwater-fed bay following precipitation. (31st December 2019) - Sankar, M.S.; Dash, Padmanava; Lu, YueHan; Paul, Varun; Mercer, Andrew E.; Arslan, Zikri; Varco, Jac J.; Rodgers, John C.
Abstract: Dissolved organic matter (DOM) often forms complexes with trace metals. The main objective of this study was to identify the sources of trace elements to a coastal bay that is fed by two blackwater rivers using DOM compositions. Surface water samples from twelve sites in Weeks Bay, Alabama were collected during four field trips and a bottom sediment sample was collected during one of the trips. Spectroscopic measurements in tandem with parallel factor analysis and multivariate statistics were used to derive DOM compositions and inductively coupled plasma mass spectrometry was used for determining trace metal concentrations. DOM chemistry and trace element concentrations together with precipitation and discharge, watershed land use and land cover data, and physicochemical parameters were used to determine the source of trace elements in the adjoining areas of the watershed to the bay and finally settling into the bay sediments. Arsenic, copper, and uranium fluxes increased while fluxes of mercury, zinc, manganese, and iron decreased following precipitation events. Concentration of all trace elements analyzed were 10, 000 times higer in the bay botton sediments than their concentrations in the water colunmn. Microbially reprocessed and soil derived DOM components increased along with the trace elements and nutrients in the bay as a result of precipitation whereas concentration of terrestrial humic-like DOM component remained the same during both dry (spring) and wet (summer and fall) periods. Principal component analysis revealed significant correlations between microbially reprocessed DOM and the trace elements including arsenic, copper and uranium indicating urban, pasture, and agricultural areas in the watershed were the sources for these trace metals. On the other hand, multiple sources were identified for manganese, zinc, and iron. Overall it was found that DOM compositions are useful for inferring the possible sources and mobility of trace elements in aquatic systems. Graphical abstract: Image 1 Highlights: Dissolved organic matter compositions were used for source-tracking trace metals. Flux of As, Cu, U, PO4, and NO3 correlated with protein-like and soil derived DOM. The trace element and DOM mobility was controlled by precipitation and discharge. Multivariate statistics revealed anthropogenic sources for the trace metals.